PENGUJIAN OPEN LEGAL POLICY MELALUI JUDICIAL REVIEW - Saputra, Agung Wirya; Suhartono, Slamet (LPPM, Universitas Muhammadiyah Riau, 2025)
In a democratic system, power is divided between the executive, legislative, and judiciary, each with its own functions and authority. Regarding judicial authority, the Supreme Court has the power to conduct judicial review, which involves testing lower regulations against the law itself. This judicial review process is important to assess whether lower regulations comply with higher laws. An interesting case of judicial review was submitted by the Garuda Party against Article 4 paragraph (1) letter d of PKPU No. 9 of 2020 concerning the Nomination for the Election of Regional Heads. In its decision, the Supreme Court ruled that Article 4 of PKPU No. 9 of 2020 lacked binding legal force and ordered the General Election Commission (KPU) to revoke it. This decision, Supreme Court No. 23 P/HUM/2024, raises questions about the authority and legality of the Supreme Court's power to revoke a regulation that should fall under the legislative authority. This contradicts the concept of open legal policy, which grants the power to form laws and regulations to the legislative body. Furthermore, the legal force of the Supreme Court's decision is also questioned, especially after the Constitutional Court issued a different ruling, No. 70/PUU-XXII/2024. The differing interpretations between the two institutions highlight a conflict in the interpretation of the same regulation.